Freeze-cast SiOC ceramics supporting the growth of industrially relevant microorganisms - Katharina Rauchenwald; Roghayeh Shirvani; Tobias Edtmaier; Matthias Steiger; Thomas Konegger (PLoS ONE, 2025)
Investigating the compatibility of ceramic support materials with industrially relevant microorganisms is a key starting point towards utilizing innovative ceramic frameworks for microbial culture support. This study demonstrates the biocompatibility of macroporous, freeze-cast SiOC monoliths with yeast Komagataella phaffii and bacteria Escherichia coli. In a first step, cultivations were carried out in the presence of non-macroporous SiOC materials pyrolyzed at 700 °C or 900 °C, which were further compared to Al2O3 and SiO2 as conventional ceramic and glass reference materials. Additionally, SiOC ceramics impregnated with 3 wt.% Cu were evaluated regarding cytotoxic effects, since Cu is recognized for its antimicrobial properties. Both E. coli and K. phaffii showed no growth inhibition in the presence of SiOC, yielding specific growth rates of 0.46 ± 0.01 h−1 and 0.088 ± 0.002 h−1, respectively, showing overall biocompatibility with SiOC. While E. coli showed growth inhibition in the presence of Cu via prolonged lag-phases, K. phaffii was resistant to Cu-modified SiOC. In the next step, adsorption of cells to macroporous SiOC was investigated after cultivation by electron microscopy of fracture surfaces of freeze-cast SiOC, structured with tert-butyl alcohol templating directional channels with pore opening diameters around 45 μm. Prevalent biofilm formation was observed within the channel walls with clear evidence for growth of K. phaffii as cell agglomerates. The study features promising results for promotion of the growth of E. coli and K. phaffii on freeze-cast SiOC ceramics, providing a versatile catalyst carrier design.